2006
DOI: 10.1037/0033-2909.132.6.959
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in trauma and posttraumatic stress disorder: A quantitative review of 25 years of research.

Abstract: Meta-analyses of studies yielding sex-specific risk of potentially traumatic events (PTEs) and posttraumatic stress disorder (PTSD) indicated that female participants were more likely than male participants to meet criteria for PTSD, although they were less likely to experience PTEs. Female participants were more likely than male participants to experience sexual assault and child sexual abuse, but less likely to experience accidents, nonsexual assaults, witnessing death or injury, disaster or fire, and combat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

164
1,134
37
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,795 publications
(1,412 citation statements)
references
References 376 publications
164
1,134
37
23
Order By: Relevance
“…Consistent with much previous research (reviewed by Olff, Langeland, Draijer, & Gersons, 2007; Tolin & Foa, 2006), women are significantly more likely to develop PTSD than are men exposed to the same traumas. We also looked at socio-economic status and marital status but found that they are not significant predictors of PTSD after controlling trauma type and respondent age–sex.…”
Section: Resultssupporting
confidence: 85%
“…Consistent with much previous research (reviewed by Olff, Langeland, Draijer, & Gersons, 2007; Tolin & Foa, 2006), women are significantly more likely to develop PTSD than are men exposed to the same traumas. We also looked at socio-economic status and marital status but found that they are not significant predictors of PTSD after controlling trauma type and respondent age–sex.…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, they seem less likely to seek help for mental health problems after trauma (Möller-Leimkühler, 2002), which may leave untreated symptoms more likely to develop to suicidality. Thirdly, following trauma, women are more likely than men to meet criteria for PTSD (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995; Tolin & Foa, 2006). PTSD has frequently been reported to be associated with suicidality and may be an important mediator in further development of suicidality after trauma (Ford & Gomez, 2015; Panagioti et al, 2015; Wilcox, Storr, & Breslau, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on how various types of traumatic event may predict suicidality (Yoo et al, 2018) is, however, still scarce, especially with regard to gender. Studies have shown that men are more likely than women to experience various types of trauma, except for sexual and violent trauma (de Vries & Olff, 2009; Tolin & Foa, 2006). Women are, however, more likely to engage in self-harm and suicide attempts than men (Nock et al, 2008; World Health Organization, 2014).…”
mentioning
confidence: 99%
“…Research has consistently found that females are more vulnerable to the development of PTSD than males (Breslau, 2009; Tolin & Foa, 2006). The present study found no gender differences in clinical post-traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…First, the method of retrospective self-report could lack validity, as self-reports may be influenced by forgetting, lack of awareness, or reporting bias related to emotional states or gender roles (Tolin & Foa, 2006). However, false negatives appear to be more common than false positives in the general population, and possible biased associations between retrospective reports of CMT and psychopathology may be the result of the rehearsal of memories, rather than bias related to current emotional states (Hardt & Rutter, 2004).…”
Section: Discussionmentioning
confidence: 99%